Biome evolution in subfamily Cercidoideae (Leguminosae): a tropical arborescent clade with a relictual depauperate temperate lineage - Hagelstam-Renshaw, Charlotte; Ringelberg, Jens J.; Sinou, Carole; Cardinal-McTeague, Warren; Bruneau, Anne (Revista brasileira de botânica, 2025)
Some plant lineages remain within the same biome over time (biome conservatism), whereas others seem to adapt more easily to new biomes. The c. 398 species (14 genera) of subfamily Cercidoideae (Leguminosae or Fabaceae) are found in many biomes around the world, particularly in the tropical regions of South America, Asia and Africa, and display a variety of growth forms (small trees, shrubs, lianas and herbaceous perennials). Species distribution maps derived from cleaned occurrence records were compiled and compared with existing biome maps and with the literature to assign species to biomes. Rainforest (144 species), succulent (44 species), savanna (36 species), and temperate (10 species) biomes were found to be important in describing the global distribution of Cercidoideae, with many species occurring in more than one biome. Two phylogenetically isolated species-poor temperate ( Cercis ) and succulent ( Adenolobus ) biome lineages are sister to two broadly distributed species-rich tropical clades. Ancestral state reconstructions on a time-calibrated phylogeny suggest biome shifts occurred throughout the evolutionary history of the subfamily, with shifts between the succulent and rainforest biomes, from the rainforest to savanna, from the succulent to savanna biome, and one early occurring shift into (or from) the temperate biome. Of the 26 inferred shifts in biome, three are closely associated with a shift from the ancestral tree/shrub growth form to a liana or herbaceous perennial habit. Only three of the 13 inferred transcontinental dispersal events are associated with biome shifts. Overall, we find that biome shifts tend to occur within the same continent and that dispersals to new continents tend to occur within the same biome, but that nonetheless the biome-conserved and biogeographically structured Cercidoideae have been able to adapt to different environments through time.